Ischemic Stroke 2021
DOI: 10.5772/intechopen.90551
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine and Ischemic Stroke

Abstract: Vinpocetine (VPN) is a synthetic ethyl-ester derivative of the alkaloid apovincamine from Vinca minor leaves. VPN is a selective inhibitor of phosphodiesterase type 1 (PDE1) has potential neurological effects through inhibition of voltage gated sodium channel and reduction of neuronal calcium influx. VPN have noteworthy antioxidant, anti-inflammatory and anti-apoptotic effects with inhibitory effect on glial and astrocyte cells during and following ischemic stroke (IS). VPN is effective as an adjuvant therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Our findings demonstrated that gentamicin-treated mice had a significant rise in MDA and a significant drop in GSH levels. El Gamal et al 38 and Al-Kuraishy et al 39 showed large increases in renal MDA and significant decreases in renal GSH in gentamicin-treated rats, which is consistent with our results. We discovered that giving celecoxib before or after gentamicin caused MDA and GSH levels in kidney tissues to be corrected to near-control values, which matched the findings of previous studies by Suddek et al 21 and Ahmed et al 1 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings demonstrated that gentamicin-treated mice had a significant rise in MDA and a significant drop in GSH levels. El Gamal et al 38 and Al-Kuraishy et al 39 showed large increases in renal MDA and significant decreases in renal GSH in gentamicin-treated rats, which is consistent with our results. We discovered that giving celecoxib before or after gentamicin caused MDA and GSH levels in kidney tissues to be corrected to near-control values, which matched the findings of previous studies by Suddek et al 21 and Ahmed et al 1 .…”
Section: Discussionsupporting
confidence: 92%
“…ASP in circulation increases substantially with overweight and obesity and declines with weight loss. ASP levels are correlated with cardiometabolic risk markers in obese people (Al-Kuraishy & Al-Gareeb, 2017;Mishra et al, 2019;Onat et al, 2017). ASP and its component proteins (C3, factor B and adipsin) have been demonstrated to be meaningfully increased in type 2 diabetes as well as in some research on type I diabetes (Cianflone et al, 2003).…”
Section: Asp and Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…[59][60][61] Nrf2 controls various genes involved in iron and heme metabolism, such as heme oxygenase one and the genes encoding the iron storage protein ferritin, to reduce the harmful effects of free iron. [62] Nrf2 is a critical factor in cellular components, which helps in cellular repair and OS control [63][64][65][66] (Figure 3). metabolites.…”
Section: Nrf2 and Cellular Metabolomicsmentioning
confidence: 99%